Medical Students’ Preference, Attitude and Perception toward Basic Medical Science Subjects in a Public University, East Malaysia - Tin, Moe Nwe; Soe, Lwin; Khin, Than Yee (a and v publications, 2021)
Introduction: Medical students build their clinical knowledge from previously obtained basic medical science knowledge during the pre-clinical year. The pre-clinical performances have some predictive value in the clinical discipline. Basic Medical Science (BMS) taught in pre-clinical years also supported the development of clinical reasoning skills and critical analysis of medical intervention. This study explored the preference, attitude and perception toward BMS subjects among the pre-clinical medical students. Materials and methods: An institution-based cross-sectional study was conducted among 189 pre-clinical students in a public university in East Malaysia by using the nine-scale statements questionnaires by West and co-workers. An independent sample t-test, one-way ANOVA, Pearson correlation and simple linear regression were used to analyze the data. Results: Among 10 BMS subjects, anatomy (29.1%) is the most preferred, followed by pathology (24.9%). Subject preference is influenced by the interesting curriculum with the highest frequency of 100%, followed by clinically useful (75.0%). The majority of students found poor attitude and perception in some items. There is no significant difference in attitude and perception toward BMS subjects between Year 1 and Year 2 students, male and female, different pre-university programs, students with scholarship and self-finance, and having family members in the medical field and those without. Conclusions and recommendation: Different teaching styles of medical faculty along with coordination with clinical departments may help the students to be more interested in learning medical education. Further study on the teaching techniques that aid in positive attitude and perception of pre-clinical students should be done.